Differences in 5-HT2A and mGlu2 Receptor Expression Levels and Repressive Epigenetic Modifications at the 5-HT2A Promoter Region in the Roman Low- (RLA-I) and High- (RHA-I) Avoidance Rat Strains - Fomsgaard, Luna (Mol Neurobiol, 2017)
The serotonin 2A (5-HT(2A)) and metabotropic glutamate 2 (mGlu2) receptors regulate each other and are associated with schizophrenia. The Roman high- (RHA-I) and the Roman low- (RLA-I) avoidance rat strains present well-differentiated behavioral profiles, with the RHA-I strain emerging as a putative genetic rat model of schizophrenia-related features. The RHA-I strain shows increased 5-HT(2A) and decreased mGlu2 receptor binding levels in prefrontal cortex (PFC). Here, we looked for differences in gene expression and transcriptional regulation of these receptors. The striatum (STR) was included in the analysis. 5-HT(2A), 5-HT(1A), and mGlu2 mRNA and [(3)H]ketanserin binding levels were measured in brain homogenates. As expected, 5-HT(2A) binding was significantly increased in PFC in the RHA-I rats, while no difference in binding was observed in STR. Surprisingly, 5-HT(2A) gene expression was unchanged in PFC but significantly decreased in STR. mGlu2 receptor gene expression was significantly decreased in both PFC and STR. No differences were observed for the 5-HT(1A) receptor. Chromatin immunoprecipitation assay revealed increased trimethylation of histone 3 at lysine 27 (H3K27me3) at the promoter region of the HTR2A gene in the STR. We further looked at the Akt/GSK3 signaling pathway, a downstream point of convergence of the serotonin and glutamate system, and found increased phosphorylation levels of GSK3β at tyrosine 216 and increased β-catenin levels in the PFC of the RHA-I rats. These results reveal region-specific regulation of the 5-HT(2A) receptor in the RHA-I rats probably due to absence of mGlu2 receptor that may result in differential regulation of downstream pathways.